Determination of essence and main objectives of regional marketing as a component in regional politics - Воронько, Т. В. (Scientific Progress & Innovations, 2012)
In the article essence and main objectives of the regional marketing specifics its functioning at modern conditions are considered. Put the accent on circumstances that restrain the development and functioning of marketing on all levels of management. It is suggested to supplement purposes of regional marketing. It should be noted that coming forward as a part of regional economic politics, the regional marketing differs in orientation on the decision of region problems and includes development and realization of conception complex development of economy and social sphere of territory, directed to the decision of its social and economic problems.